PENGARUH PENGGUNAAN PEKERJAAN AUDIT INTERNAL DAN ATURAN ETIKA TERHADAP KUALITAS AUDIT (Studi Pada Kantor Akuntan Publik Provinsi DKI Jakarta) - , Novita, Muhammad Ramadhan , Andreas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2023)
The purpose of this study was to examine effect of the use of internal audit work and ethical rules on audit quality. This study used the questionnaire method, which is a data collection method by asking questions to be answered by respondents. The research sample was 80 auditors working at the DKI Jakarta Province public accounting firm registered with IAPI in 2020. The sampling method in this study was quota sampling. Hypothesis testing is done using Bootstrapping analysis (Path Coefficient, Inner Model). The statistical test tool used is the SmartPLS Ver.3.3.2 for Windows 2020 program.The results of the study show that the use of internal audit work and ethical rules have an effect on audit quality. Keywords: Internal audit work, ethical rules, audit quality